PENYULUHAN TENTANG MANFAAT BATANG SERAI (Cymbopogon Citratus) BAGI PASIEN INSOMNIA DI RUMAH SAKIT SEMBIRING - Nina Irmayanti Harahap; Sofia Rahmi; Palas Tarigan (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
A condition characterized by a disturbance in the amount, quality or time of sleep in an individual is often referred to as insomnia. Sleep disturbances can interfere physically, emotionally, cognitively, and socially in adults. The magnitude of the possibility of academic, emotional, health, and behavioral problems in adults can be prevented or corrected, this fact shows significantly through intervention, through improving the quality and quantity of sleep by having the advantages of lemongrass aromatherapy which without causing side effects at all is able to overcome the reduction of insomnia. Citronella essential oil has been used for centuries to reduce rashes, inflammation, infection, pain and other health conditions. The method used through health education is aimed at achieving changes in the behavior of individuals, families and communities in fostering and maintaining health, playing an active role in optimizing health in accordance with healthy living physically, mentally and socially. Providing counseling with the method used is the lecture method by explaining and explaining an understanding, idea or message orally to the target group.